The relationship between sleep duration and frailty: findings from the China Health and Retirement Longitudinal Study - Huang, Liyan; He, Xiaofang; Zuo, Yao; Yang, Hui; Zhang, Lin (Frontiers in Public Health, 2024)
BackgroundResearch investigating the association between sleep duration and the risk of frailty has yielded conflicting results. This study used data from the China Health and Retirement Longitudinal Study (CHARLS) to investigate the association between sleep duration and frailty.MethodsParticipants aged 45 and above at baseline were included in this study. Night or total sleep was categorized into three groups: short (<6 h), normal (6–9 h), and long sleep duration (≥9 h). Frailty was measured by a 31-item frailty index (FI). Non-frail participants at baseline were followed up after a 7-year period. The association between sleep duration and FI was examined by linear regression and restricted cubic spline (RCS) analysis. The relationship between sleep duration and the risk of frailty was evaluated using multinomial logistic regression analysis.ResultsA total of 10,258/10,250 (night/total sleep duration) participants were included in the cross-sectional study and 4,770/4,768 in the longitudinal study. A negative correlation was identified between the both night and total sleep duration and FI (night: β = −0.83, p < 0.001; total: β = −0.66, p < 0.001) after adjusting for age, sex, education level, marital status, residence, yearly expenditure, BMI, waist circumference, smoking status, and drinking status in the cross-sectional study. In the longitudinal study, the relationship remained. Short sleep duration increased FI (night: β = 3.59, p < 0.001; total: β = 3.74, p < 0.001) and the risk of frailty (night: OR [95% confidence interval (CI)], 1.06 [1.05, 1.08], p < 0.001; total: 1.07 [1.06, 1.08], p < 0.001) compared to normal sleep duration in the fully adjusted model of the cross-sectional study. The result remains consistent in the longitudinal analysis.ConclusionShort sleep duration increases the risk of frailty in Chinese individuals aged 45 and above. Extending sleep duration in this population may help prevent or alleviate frailty among middle-aged and older adult individuals.